2006
DOI: 10.1038/sj.cgt.7700961
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of melanoma therapy with dendritic cells transfected with autologous tumor-mRNA

Abstract: We have developed an individualized melanoma vaccine based on transfection of autologous dendritic cells (DCs) with autologous tumor-mRNA. Dendritic cells loaded with complete tumor-mRNA may generate an immune response against a broad repertoire of antigens, including unique patient-specific antigens. The purpose of the present phase I/II trial was to evaluate the feasibility and safety of the vaccine, and the ability of the DCs to elicit T-cell responses in melanoma patients. Further, we compared intradermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(108 citation statements)
references
References 43 publications
3
100
0
2
Order By: Relevance
“…The analysis suggests a difference in favor of this study treatment, reaching a borderline statistical significance. However, we have previously observed that human responses frequently do not follow a Th1/Th2 delineation (23,28,29). The present responses comprised high levels of key Th1-cytokines IFNg and TNFa, but also of hallmark Th2 cytokines, interleukin 5 (IL-5) and IL-13.…”
Section: Cytokine Profilesmentioning
confidence: 95%
“…The analysis suggests a difference in favor of this study treatment, reaching a borderline statistical significance. However, we have previously observed that human responses frequently do not follow a Th1/Th2 delineation (23,28,29). The present responses comprised high levels of key Th1-cytokines IFNg and TNFa, but also of hallmark Th2 cytokines, interleukin 5 (IL-5) and IL-13.…”
Section: Cytokine Profilesmentioning
confidence: 95%
“…One is based on adoptive transfer of autologous dendritic cells (DCs) transfected ex vivo with antigen-encoding RNA. [5][6][7] The other employs direct injection of naked RNA. 8,9 Feasibility and safety of vaccination protocols based on intradermal administration of naked RNA have been shown in preclinical and clinical settings and partial protection from tumor challenge has been achieved in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Therapy with tumor RNA-loaded DC vaccines induces T cell responses specific for the transfected antigens in about 50% of melanoma patients [33]. Earlier studies have shown that activated human B cells can be loaded with RNA and efficiently lead to antigen-specific T cell responses against antigens present in vitro [13,14]; however, the ability of RNA-loaded B cells to activate T cells in vivo has not been reported.…”
Section: Discussionmentioning
confidence: 99%